2012
DOI: 10.1002/hfm.20302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and critique of Healthcare Failure Mode and Effect Analysis applied in a radiotherapy case study

Abstract: Healthcare Failure Mode and Effect Analysis (HFMEA®) has been developed to support the proactive analysis of health care treatment processes. Its use has been reported in several studies with both positive and negative comments regarding the quality of the results and the efficacy of the method. This paper examines the HFMEA® methodology and discusses the challenges that were encountered during its application to a proactive analysis of radiotherapy patient record systems in a large public hospital. Several we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…First, the categories for frequency of occurrence are changed into easily defined categories in order to prevent team members from placing their own interpretation on the categories. [11][12][13][14][15][16][17][18][19] For instance, categories such as "less than once a year," "yearly," "monthly," "quarterly," and "weekly" are used instead of HFMEA™ categories such as "remote," "uncommon," "occasional," and "frequent." Second, the numbers in the HFMEA Hazard Scoring Matrix™ are replaced by arbitrary risk scale such as very low, low, high, and very high with accompanying red or green box, while the HFMEA™ originally used a numerical classification with more discrete levels that allows for more subtle differentiation between risks.…”
Section: Scorementioning
confidence: 99%
See 3 more Smart Citations
“…First, the categories for frequency of occurrence are changed into easily defined categories in order to prevent team members from placing their own interpretation on the categories. [11][12][13][14][15][16][17][18][19] For instance, categories such as "less than once a year," "yearly," "monthly," "quarterly," and "weekly" are used instead of HFMEA™ categories such as "remote," "uncommon," "occasional," and "frequent." Second, the numbers in the HFMEA Hazard Scoring Matrix™ are replaced by arbitrary risk scale such as very low, low, high, and very high with accompanying red or green box, while the HFMEA™ originally used a numerical classification with more discrete levels that allows for more subtle differentiation between risks.…”
Section: Scorementioning
confidence: 99%
“…Both FMEA and m-HFMEA include five steps: (1) define the topic, (2) assemble the team, (3) develop a process map for the process consecutively numbering each step and substep of that process, (4) conduct the risk analysis, and (5) develop actions and outcomes. [11][12][13][14][15][16][17][18][19] In m-HFMEA, the fourth step has four substeps: (4a) identifying failure modes, (4b) identifying the causes of these failure modes, (4c) scoring each failure mode using the risk inventory matrix, and (4d) conducting a Decision Tree™ analysis. Each failure mode was identified in terms of severity (S) and frequency (F).…”
Section: Scorementioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Recently, FMEA was proposed for use in the quality assurance of radiation therapy by Huq et al, 9,10 and its use in photon radiation therapy QA has been reported in many publications. [11][12][13][14][15][16][17][18][19] However, the literature on the use of FMEA in proton therapy is scarce. Cantone et al analyzed potential errors in the treatment planning stage for a pencil beam proton scanning system.…”
Section: Introductionmentioning
confidence: 99%